Pengaruh Model Iklan Terhadap Citra Merek Produk Pond’s - Sharah Adella R; Qoute Nuraini C; Layung Paramesti (UNIVERSITAS PAKUAN, 2019)
AbstractThe study conducted to identify the effect of celebrity endorser on brand image. This study uses quantitative methods with techniques used are questionnaire and literature study. The questionnaires spread to 100 respondents, respondents selected were instagram followers @pondsindonesia. Theory used is Uses and Gratification because it said that the community has full power in choosing, viewing and reading the contents of media in order to satisfy their needs. The study uses simple linear regression technique with the result says that there is a significant influence of the celebrity endorser on brand image.Keywords: advertising, brand image, celebrity endorser